Prehospital paediatric emergency care: paediatric triage. Issue 11 (22nd October 2009) - Sandell, J M; Maconochie, I K; Jewkes, F
Abstract : The practice of triage was conceived during the Napoleonic wars, with the aim of salvaging those soldiers whose injuries were readily treatable, returning them to the battlefield at the earliest opportunity. Literally, the word triage means "to sieve" or "to sort" (French trier ), and those earlier battlefield principles have been refined and expanded to now encompass trauma and medical emergencies, with triage practiced in prehospital and hospital settings. To address the anatomical, physiological and developmental differences encountered when dealing with children, specific paediatric triage systems have also been developed, and this article discusses their merits.